PENGARUH CITRA MEREK, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG (Studi Kasus Mahasiswa Universitas Sriwijaya Indralaya) - Doni Defriansyah; Islahuddin Daud; Welly Nailis (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2016)
This research aims to know the influence of brand, price, and quality of product toward buying decision Samsung smartphone partially and stimultanously. Independent variable in this research was brand (X1), price (X2), and quality of product (X3) and dependent variable was buying decision (Y). Technique for sampling in this research was Purposive Sampling. Questionnaire distributed to Sriwijaya University student in Indralaya about 100 respondent. Technique for analyzing the data in this research was using multiple linier regression, F test and t test. The result of this reseach showed that brand, price, and quality of product stimultanously has significant influence toward buying decision nevertheless, partially, only price which did not significantly influence the buying decision. Keywords: Brand, Price, Quality of Product, Buying decision